2010
DOI: 10.5897/ajb09.1555
|View full text |Cite
|
Sign up to set email alerts
|

Nanobiotechnology for the production of biofuels from spent tea

Abstract: Bioenergy is the only alternative and cheap source of energy which can be made easily available to the world. The present experiment included three steps for the conversion of spent tea (Camellia sinensis) into biofuels. In the first step, spent tea was gasified using Co nano catalyst at 300°C and atmospheric pressure. Catalytic gasification of spent tea yielded 60% liquid extract, 28% fuel gases and 12% charcoal. Gaseous products contain 53.03% ethene, 37.18% methanol and 4.59% methane. In the second step of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Mahmood and Hussain reported After wasted tea was gasified catalytically, 60% liquid extract, 28% fuel gases, and 12% charcoal were produced. 53.03% ethene, 37.18% methanol, and 4.59% methane are found in gaseous products [ 113 ]. A nanotechnology-based approach might complement an environmentally friendly agricultural production method [ 114 ].…”
Section: Nanotechnology In Sustainable Agriculturementioning
confidence: 99%
“…Mahmood and Hussain reported After wasted tea was gasified catalytically, 60% liquid extract, 28% fuel gases, and 12% charcoal were produced. 53.03% ethene, 37.18% methanol, and 4.59% methane are found in gaseous products [ 113 ]. A nanotechnology-based approach might complement an environmentally friendly agricultural production method [ 114 ].…”
Section: Nanotechnology In Sustainable Agriculturementioning
confidence: 99%
“…As a result, the approaches are expensive and often insufficient in eliminating nanocatalysts from the reaction mixture. 140…”
Section: Challenges and Opportunities Of Using Nanoparticles In Biofu...mentioning
confidence: 99%
“…They reported that biodiesel yield from waste cooking oil was lower compared to palm oil as a result of towering water content that led to substrate hydrolysis and subsequently a cut down on yield [68; 69]. Ademiluyi and Mepba examined the ethanol yield and properties of five different cassava flours [70]. They investigated the effect of yeast quantity, cassava flour converted to acid, mineralized media ratio of ethanol yield, and the physical characteristics of ethanol produced from the several cassavas.…”
Section: Effect Of Production Process On Yieldmentioning
confidence: 99%
“…Hence, records for better perspective on collection and planning for most renewable residue is necessary to meet biofuel targets. Yaakob et al, 2013, Chen et al, 2009, Mahmood and Hussain, 2010, Papanikolaou et al, 2011, Pleissner et al, 2013 reported that food wastesare converted to fatty acids and biodiesel using trans-esterification of microbial oils produced by various oleaginous microorganisms. Figure 4 highlights the different phases of world food wastages in the food supply chain.…”
Section: Biofuel From Residual Wastesmentioning
confidence: 99%